English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

16 answers

Double the second equation and subtract the first from it:

8x + 8y = 120
1x + 8y = 60
-----------------
7x = 60
x = 60/7

60/7 + 8y = 60
8y = (420 - 60) / 7 = 360/7
y = 360/56 = 45/7

2006-11-22 19:26:31 · answer #1 · answered by Jim Burnell 6 · 1 0

x+8y=60 => x=60-8y 4x+4y=60 => x+y=15 => x=15-y because of the fact the x values for the two the equations are the comparable, we are able to write: 60-8y = 15-y 60-15 = 8y-y 40 5 = 7y y = 40 5/7 y = 6 3/7 Substi y = 6 3/7 into x=15-y, x = 15 - 6 3/7 = 8 4/7 So x = 8 4/7 and y = 6 3/7

2016-11-26 02:44:32 · answer #2 · answered by ? 4 · 0 0

It can be solved in different ways like:
divide the second equation by 4 and it will be:
x + y =15
then subtract it from the first equation:
x + 8y =60
-x + y =15
the answer would be:
9y =45
divide both sides by 9 and you'll get:
y =5
use either of the both equations to find x (I think the first is much more easier because you don't multiply a lot) and substitute it to y:
x + 8(5) =60
x + 40 =60
then subtract 40 from both sides:
x + 40 - 40 =60 - 40
then you obtained x =20

You can also do the other way:
double the second equation then it will be like this:
8x+8y =120
then do the steps just like in the first example:
8x - 8y =120
- x + 8y =60
then:
7x =60
divide both sides and you'll obtain x =60/7
substitute and you'll get y =45/7
try to check those answers and you'll find that they're both correct. sorry if that doesn't help so much but you can ask me if you had any other questions on math. I'm not that good on the subject but I still can help you.

2006-11-22 21:40:49 · answer #3 · answered by darkwizard_71 2 · 0 0

x+8y=60 => x=60-8y
4x+4y=60 => x+y=15 => x=15-y

As the x values for both the equations are the same, we can write:

60-8y = 15-y
60-15 = 8y-y
45 = 7y
y = 45/7
y = 6 3/7

Substi y = 6 3/7 into x=15-y,
x = 15 - 6 3/7 = 8 4/7

So x = 8 4/7 and y = 6 3/7

2006-11-26 02:42:45 · answer #4 · answered by Kemmy 6 · 0 0

x + 8y = 60- - - - - -Equation 1
4x + 4y = 60- - - - -Equation 2
- - - - - - - - -
Substitute Method equation 1

x + 8y = 60
x + 8 y - 8 y = 60 - 8y
x = 60 - 8 y

Insert the x value into equation 2

- - - - - - - - - - - - - - - - - - - -

4x + 4y = 60

4(60 - 8y) + 4y = 60

240 - 32y + 4y = 60

240 - 28y = 60

240 - 28y - 240 = 60 - 240

- 28y = - 180

- 28y/-28 = - 180/-28

y = 6 12/28

y = 6 3/7

y = 6.428571429

The answer is y = 6.48571429

Insert the y valut into equation 1

- - - - - - - - - - - - - - - - - - - - - -

x + 8y = 60

x + 8(6.428571429) = 60

x + 51.42857143 = 60

x + 51.42857143 - 51.42857143 = 60 - 51.42857143

x = 8.571428571

The answer is x = 8.571428571

Insert the y value into equation 1

- - - - - - - - - - - - - - - - - - - - - -

x + 8y = 60

8.571428571 +8(6.428571429) = 60

8.571428571 + 51.42857143 = 60

60 = 60

- - - - - - - - -

4x + 4y = 60

4(8.571428571) + 4(6.428571429) = 60

34.28571438 + 25.71428572 = 60

60 = 60

- - - - - - - -s-

2006-11-22 22:57:57 · answer #5 · answered by SAMUEL D 7 · 0 0

x + 8y = 60
4x + 4y = 60 eliminate 'y' by multiplying
by -2 - hence

x + 8y = 60
-8x -8y = -120 'add' these two equations

-7x = -60
x = 60/ 7 (This improper fraction is acceptable).
Substituting this value (60/7) in to the first eq'n

60/7 + 8y = 60 =>
60 + 56y = 420
56y = 420 - 60
56y = 360
14y = 90
7y = 45
y = 45/7

Ans; x = 60/7 AND Y = 45/7

2006-11-26 07:31:38 · answer #6 · answered by lenpol7 7 · 0 0

x + 8y =60 and 4x + 4y =60
=>x + 8y =60 and 8x + 8y =120
{x + 8y =60} - {8x + 8y =120}
=>{x - 8x} + {8y-8y} = {60 - 120}
=> -7x = -60
=> x = 60/7
Now, x + 8y =60 and x = 60/7
=> (60/7) + 8y = 60
=> 8y = 60 - (60/7)
=> y = {60 - (60/7)}/8 = 360/56 = 45/7

So, answer is (x,y) = (60/7, 45/7)

2006-11-22 20:36:30 · answer #7 · answered by Paritosh Vasava 3 · 0 0

4x + 4y =60=>4(x+y)=4x15=>x + y =15 |
|=>(x+8y) - (x + y) = 45
x + 8y =60|
=>7y = 45=>y =45:7 =6,428....
x+8y = 60=>x =60 -(45:7x8)=>x=60-360:7=>x=(420-360):7=
=60 : 7=8,571.....

2006-11-22 20:43:25 · answer #8 · answered by andrei_chuky 1 · 0 0

X=8.569
y=6.429

x+8y=60
Move the 8y to leave x on one side and the problem on the other
x=60-8y
Now take the second equation and plug in 60-8y for x
4(60-8y)+4y=60
4*60=240
4*8y=32y
240-32y=4y=60
Combine like terms
240-28y=60
Combine like terms again
-28y=60-240
-28y=-180
Divide by -1 on both sides to flip the signs
28y=180
Divide each side by 180 to get y=6.429

Now solve for x.
x+8(6.429)=60
x+51.432=60
Combine like terms
x=60-51.432
x=8.569

2006-11-22 20:01:13 · answer #9 · answered by -L 3 · 0 0

x+8y=60........(1)
4x+4y=60......(2)
multiply (2) by 2
8x+8y=120
subtract (1) from(2)
7x=60
x=60/7
substitute x into (1)
60/7+8y=60
multiply by 7
60+56y=420
56y = 360
y=45/7

therefore, x=60/7 and y=45/7

mikeyg has also got the right
answer

i hope that this helps

2006-11-22 19:51:38 · answer #10 · answered by Anonymous · 0 0

fedest.com, questions and answers